Penyampaian Akta Pemberian Hak Tanggungan Secara Elektronik Menurut Perspektif Perundang-Undangan Di Indonesia - Waffy, Muhammad; Syamsir, Syamsir (Universitas Batanghari Jambi, 2023)
The responsibility of the Land Office if there is a problem with the IT system or HT-el application is only technical responsibility by providing access to the PPAT/Bank as the creditor to communicate directly with the local Land Office employees in the Electronic Mortgage registration service section via the Whatsaap application and can also come by. go directly to the land office and Obstacles with PPAT are: 1). Corrections carried out by the Land Office on files that have been uploaded by PPAT often occur in a short time. 2). The HT-el application often experiences problems or server errors which usually occur during working hours. 3). Insynchronization between the physical data of the Certificate and the data in the Land Office's electronic system. 4). The certificate is not ready when it is uploaded, it has not been validated, it has not been deployed. 5). Banks as creditors need to always be reminded to immediately carry out the Mortgage Rights registration process. 6). HT-el services do not provide access to land that has not been certified and the obstacles for banks as creditors are: 1). Server errors often occur in Ht-el partner applications. 2). In the roya process, there is often a lack of synchronization between the roya records on the physical certificate and the records contained in the Land Office's electronic system. 3). In the Roya process, there are many processes that cannot be done with a computer, you have to use a cellphone first.